Implementasi Sistem Pengendali Rumah Pintar Menggunakan Laravel - Laila Khoirunnisa Nurul Imani; Nanda Alicia; Fahmizal Fahmizal; Unan Yusmaniar Oktiawati (Departemen Teknik Elektro dan Informatika Sekolah Vokasi UGM, 2020)
The control of household electronic equipment can now be done remotely using a website, or better known as the smart home controller application to reduce waste of electricity usage. The electronic equipment that is controlled changes the lights and sockets. This electronic equipment controller website is made with the Laravel framework which uses the PHP 5.8 programming language which is closed, therefore a connection is made with the REST API that uses the Javascript programming language to bridge the communication between electronic equipment and the website. Delivery of data between the website and components requires a server and broker to broker data paths. Thus MQTT is needed as a means of exchanging data on the hardware side so it requires a gateway in the form of Node Js to connect PHP with MQTT. Test results are done by testing the speed of the lights using various internet connection media. The test results showed the fastest internet connection media, namely using a laptop connected to a WiFi internet network with an average speed of 0.691 seconds. The smart home controller website named Pantaw can be accessed using the UGM hotspot WiFi network.Keywords: Website, smarthome, MQTT, Laravel, Node Js.